2019
DOI: 10.1002/nav.21859
|View full text |Cite
|
Sign up to set email alerts
|

Interdiction models for delaying adversarial attacks against critical information technology infrastructure

Abstract: Information technology (IT) infrastructure relies on a globalized supply chain that is vulnerable to numerous risks from adversarial attacks. It is important to protect IT infrastructure from these dynamic, persistent risks by delaying adversarial exploits. In this paper, we propose max‐min interdiction models for critical infrastructure protection that prioritizes cost‐effective security mitigations to maximally delay adversarial attacks. We consider attacks originating from multiple adversaries, each of whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 43 publications
1
7
0
1
Order By: Relevance
“…Based on the result, the lack of learning equipment tools and resource in new pedagogical approaches is a major challenge encountered in integrating MIS in secondary schools. This finding is related to the report by Zheng and Albert [16] who observed that inadequate technology infrastructure, resource materials, and other basic tools for effective teaching makes learning difficult. Jones [6] posits that individual teachers who possessed less than upper secondary education are considerably less likely to use computers for a range of reasons.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Based on the result, the lack of learning equipment tools and resource in new pedagogical approaches is a major challenge encountered in integrating MIS in secondary schools. This finding is related to the report by Zheng and Albert [16] who observed that inadequate technology infrastructure, resource materials, and other basic tools for effective teaching makes learning difficult. Jones [6] posits that individual teachers who possessed less than upper secondary education are considerably less likely to use computers for a range of reasons.…”
Section: Discussionsupporting
confidence: 56%
“…While items 21, 24, 25, and 28 having a mean score below 2.50 and corresponding standard deviation of 1.18, 1.16, 0.64, and 1.30 were rejected by male teachers. Similarly, items 11,12,13,14,16,17,18,19, and 20 having a mean score above 2.50 and corresponding standard deviation of 0.98, 0.71, 0.78, 1.03, 1.00, 1.22, 0.78, and 0.69 were all accepted by female teachers. While items 14 and 15 having a mean score of 2.42 and 2.42 corresponding to standard deviation of 0.75 and 1.19 were rejected by female teachers.…”
Section: Research Questions 3: What Are the Strategies For Effective ...mentioning
confidence: 94%
“…Prevention or mitigation techniques include anything traditionally used against adversarial attacks, such as organisational measures, encryption and other classic measures. Of particular interest is mitigation at scale and through simulations and modelling [51,50].…”
Section: Supply Chain Attacksmentioning
confidence: 99%
“…As is the lack of deliberately abstract guidance which, like Denmark, does not exist. Definitions of operators of essential services and what is otherwise needed are here, but one noticeable difference is clear, as fines and investigations are done through either designated authorities 51 or authorized officers 52 . The latter is interesting, but does not mean there will be differences in enforcement, which is found in Reg 34.…”
Section: Irelandmentioning
confidence: 99%
“…Для розв'язання такої задачі пропонується евристична декомпозиція. Дворівнева оптимізація також використовується для проекту перехоплення, у якому особи, які приймають рішення, розгортають заходи, спрямовані на максимальні затримки множинних ворожих атак, коли тривалості затримки є невизначеними [59]. 100 ISSN 1028-0979 Оскільки в реальних задачах не завжди всі параметри відомі напевне, пропонуються моделі стохастичної оптимізації [60], зокрема модель вибору портфеля засобів контролю безпеки з урахуванням середнього та найменшого значень міри ефективності [61,62].…”
Section: оптимізація критичних інфраструктурunclassified